A novel technique of minimally invasive calcaneal osteotomy for intractable insertional Achilles tendinopathy associated with Haglund deformity. Issue 5 (July 2022) - Choi, Jun Young; Suh, Jin Soo
Abstract: Background: To date, minimally invasive surgery (MIS) involving calcaneal osteotomy for Haglund deformity associated with intractable insertional Achilles tendinopathy has not been reported. This study presents the radiographic and clinical outcomes of our novel MIS-dorsal closing wedge calcaneal osteotomy (DCWCO) technique compared to open Haglund resection. We hypothesized that earlier clinical improvement after MIS-DCWCO could be achieved by leaving the Achilles tendon insertion site untouched. Methods: We retrospectively reviewed and compared the clinical and radiographic parameters of patients who underwent MIS-DCWCO (11 cases) or open Haglund resection (14 cases) between January 2012 and June 2019. The minimum duration of follow-up for inclusion was 18 months. We measured the calcaneal pitch, Meary's, Fowler-Philip, and Böhler's angles. Clinical outcomes were evaluated using the visual analogue scale (VAS) and Victorian Institute of Sports Assessment-Achilles (VISA-A) scores measured preoperatively and at 3, 6, 9, 12, and ≥18 months, postoperatively. Results: In both groups, the Meary's and calcaneal pitch angles did not change significantly, whereas the Fowler-Philip and Böhler's angles were significantly changed postoperatively. Significant improvements in VAS and VISA-A scores were observed in both groups ( P < 0.001). The extent of correction of the four radiographic and two clinical parameters were not significantly different between the two groups. However, VAS and VISA-A scores at postoperative 6 months were significantly different, whereas these parameters were not significantly different at all other time points. Conclusion: Both techniques provided similar postoperative clinical and radiographic improvement. However, MIS-DCWCO achieved earlier clinical improvement than open Haglund resection. Level of evidence: Level III, comparative series.